2009
DOI: 10.1177/1750635209104651
|View full text |Cite
|
Sign up to set email alerts
|

Don't shoot the messenger: prospects for protecting journalists in conflict situations

Abstract: One of the greatest threats to freedom of expression around the world is the violence committed against journalists practicing their profession in conflict situations. During the last 20 years, an alarming number of journalists have been targeted or killed when reporting about war. This situation has prompted several international organizations to offer suggestions on how to protect the messengers who report about war. In this study, the authors provide a historical overview of journalist protection. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…This has had implications for coverage of crisis events over time with a greater degree of misinformation tending to be shared between confirmed reports (Deavours, 2020). Deavours (2020) compared the Sandy Hook school shooting with news coverage of 9/11, with an interest in the journalistic norm of neutrality-a norm journalists struggled to enact not only in the dissemination of the facts of the event themselves but also given concerns for their own safety in onscene reporting situations (Henrichsen, 2021;Lisosky & Henrichsen, 2009). Deavours' study (2020) demonstrates that enacting neutrality primarily became difficult in light of discussing policy decisions, more so even than in discussing the deaths resulting from the school shooting event.…”
Section: News Coverage Of School Shootingsmentioning
confidence: 99%
“…This has had implications for coverage of crisis events over time with a greater degree of misinformation tending to be shared between confirmed reports (Deavours, 2020). Deavours (2020) compared the Sandy Hook school shooting with news coverage of 9/11, with an interest in the journalistic norm of neutrality-a norm journalists struggled to enact not only in the dissemination of the facts of the event themselves but also given concerns for their own safety in onscene reporting situations (Henrichsen, 2021;Lisosky & Henrichsen, 2009). Deavours' study (2020) demonstrates that enacting neutrality primarily became difficult in light of discussing policy decisions, more so even than in discussing the deaths resulting from the school shooting event.…”
Section: News Coverage Of School Shootingsmentioning
confidence: 99%
“…We have found three limitations in previous studies of journalist safety. First, we found that most studies on the safety of journalists stemmed out of conflict and reporting of war zones (Ashry, 2019;Aslam, 2015;Creech, 2018;Düsterhöft, 2013;Eide, Khalvatgar, & Shirzad, 2019;Greppi, 2004;Høiby & Ottosen, 2017;Kim, 2010;Lisosky & Henrichsen, 2009;Relly & Bustamante, 2014;Saboory et al, 2017;Tumber, 2006). Journalists' safety in stable authoritarian or hybrid regimes like Bangladesh hardly gets scholarly attention.…”
Section: The Scope Of This Study: Safety Of Journalists In Bangladeshmentioning
confidence: 99%
“…KEYWORDS: Gaza Strip, human security, news media, Palestinian journalists, press freedom, West Bank Introduction Scholars, global press rights groups, and other organizations around the world have documented an increase in insecurity among journalists when carrying out their work (Bjørnskov and UNESCO 2016UNESCO , 2018. Most research on insecurity and risk has focused on violence against journalists or news media and their work in conflict zones (Høiby and Ottosen 2017; Hughes and Márquez-Ramírez 2017; Kim and Hama-Saeed 2008;Lisosky and Henrichsen 2009) or "insecure democracies" (Hughes et al 2017b, 645). This exploratory study uses a challenging case to further analyze other types of insecure environments that journalists face in their occupation and, perhaps more important, to examine necessary conditions for journalists to perform work in the public interest.…”
mentioning
confidence: 99%